Isolation and Characterisation of Endophytic Nitrogen Fixing Bacteria in Sugarcane - Ampiga Muangthong; Somchit Youpensuk; Benjavan Rerkasem (Tropical Life Sciences Research, 2015)
Endophytic nitrogen fixing bacteria were isolated from the leaves, stems and roots of industrial variety (cv. U-Thong 3; UT3), wild and chewing sugarcane plants grown for 6 weeks in nitrogen (N)-free sand. Eighty nine isolates of endophytic bacteria were obtained on N-free agar. An acetylene reduction assay (ARA) detected nitrogenase activity in all 89 isolates. Three isolates from the chewing (C2HL2, C7HL1 and C34MR1) sugarcane and one isolate from the industrial sugarcane (UT3R1) varieties were characterised, and their responses to different yeast extract concentrations were investigated. Three different responses in nitrogenase activity were observed. Isolates C2HL2 and C7HL1 exhibited major increases with the addition of 0.005% yeast extract, C34MR1 exhibited no response, and UT3R1 exhibited a significant decrease in nitrogenase activity with 0.005% yeast extract. In all the isolates, nitrogenase activity decreased with further increase of the yeast extract to 0.05%. The highest nitrogenase activity was observed in isolates C2HL2 and C7HL1, which had 16S rRNA gene sequences that were closely related to Novosphingobium sediminicola and Ochrobactrum intermedium, respectively. Bakteria pengikat nitrogen endofit telah diasingkan daripada daun, batang dan akar pokok tebu jenis industri (cv. U-Thong 3; UT3), liar dan kunyah yang telah bertumbuh selama 6 minggu dalam pasir bebas nitrogen (N). Lapan puluh sembilan pencilan bakteria endofit telah didapati daripada agar bebas N. Cerakin penurunan asetilena (ARA) telah mengesan aktiviti nitrogenase dalam kesemua 89 pencilan. Ciri-ciri tiga pencilan daripada tebu jenis kunyah (C2HL2, C7HL1 and C34MR1) dan satu daripada jenis industri (UT3R1) dan respons terhadap extrak yis yang berbeza kepekatan telah dikaji. Tiga respons aktiviti nitrogenase berlainan telah diperhatikan. Pencilan C2HL2 dan C7HL1 menunjukkan peningkatan major dengan penambahan ekstrak yis sebanyak 0.005%, C34MR1 tidak menunjukkan sebarang respons, dan C7HL1 menunjukkan pengurangan yang signifikan dalam aktiviti nitrogenase dengan penambahan ekstrak yis sebanyak 0.005%. Dalam kesemua pencilan, aktiviti nitrogenase berkurangan dengan peningkatan yis ekstrak hingga 0.05%. Aktiviti nitrogenase tertinggi diperhatikan dalam pencilan C2HL2 dan C7HL1, yang mempunyai jujukan gen 16S rRNA yang menyerupai Novosphingobium sediminicola dan Ochrobactrum intermedium, masing-masing.